Spatially resolved analysis of the T cell immune contexture in lung cancer-associated brain metastases - Richa Gupta; Sarah B Goldberg; Kurt A Schalper; Harriet M Kluger; Lucia B Jilaveanu; Adebowale J Adeniran; Benjamin Y Lu; Adam Aguirre-Ducler; Nicole Gianino; Hailey Wyatt; Matthew Ribeiro; Veronica L Chiang; et al. (Journal for ImmunoTherapy of Cancer)
Despite unique genetic alterations within brain metastases (BrMs) and an immunologically distinct surrounding microenvironment, the composition and functional properties of tumor-infiltrating lymphocytes within BrM remain largely unexplored. In particular, the expression of coinhibitory receptors, such as programmed cell death 1 (PD-1), T cell immunoglobulin mucin receptor 3 (TIM-3), and lymphocyte activation gene 3 (LAG-3), within BrMs is unknown. Using multiplexed quantitative immunofluorescence (QIF), this study evaluates the localized expression of PD-L1, level and functional profile of major T cell subsets, and coinhibitory receptors within lung cancer-associated BrMs and primary lung tumors. Clinicopathologically annotated samples from 95 patients with lung cancer between 2002 and 2015 were represented in a tissue microarray format. Spatially resolved and multiplexed QIF was used to evaluate PD-L1 protein, phenotype markers for major T cell subsets (CD3, CD4, CD8, and FOXP3), cell-localized activation and proliferation markers (granzyme B and Ki67), and coinhibitory receptors (PD-1, LAG-3, and TIM-3). The signal for each marker was measured in marker-selected tissue compartments, and associations between marker levels, tumor location, and major clinicopathological variables were studied. In total, 41 primary lung tumors and 65 BrMs were analyzed, including paired samples from 11 patients. Levels of tumor PD-L1 expression were comparable between BrMs and primary lung tumors. BrMs had significantly lower levels of all T cell subsets relative to primary lung tumors, and T cells in BrMs displayed lower levels of granzyme B than primary lesions. PD-1, TIM-3, and LAG-3 levels in CD3+ T-cells were also significantly lower in BrMs. Marker expression in patients with paired samples from BrMs and primary lung tumors showed comparable results. High CD3+ T-cells, as well as high levels of TIM-3 and LAG-3 in CD3+ T-cells, were associated with longer overall survival in BrMs but not primary lung tumors. Lung cancer-associated BrMs display lower T cell infiltration, markers of cytolytic function, and immune regulatory signals than primary lung tumors. Despite these differences, high TIM-3 and high LAG-3 expressions in CD3+ T-cells were associated with longer survival. These features are accompanied by comparable levels of PD-L1 protein expression compared with primary lung tumors. These results highlight unique aspects of the tumor immune microenvironment within the brain and provide further support for intracranially focused therapies.